Angie made an error in the last step of her solution where she wrote \( x = -18 \).
Let's examine the solution step-by-step:
-
Start with the equation: \[ -x + 7 = -11 \]
-
Subtract 7 from both sides: \[ -x + 7 - 7 = -11 - 7 \] Simplifying this gives: \[ -x = -18 \]
-
To solve for \( x \), we need to multiply both sides by -1: \[ x = 18 \]
The mistake was that she neglected to change the sign of \( x \) when moving to the final answer. Thus, the correct solution is \( x = 18 \), not \( x = -18 \).